2006
DOI: 10.4049/jimmunol.177.12.8874
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis-induced CXCR4 and chemokine expression leads to preferential X4 HIV-1 replication in human macrophages

Abstract: tuberculosis-induced CXCR4 and chemokine expression leads to preferential X4 HIV-1 replication in human macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 0 publications
1
23
0
3
Order By: Relevance
“…After a final wash, the samples were mounted with VectraShield mounting medium (Vector Laboratories), and images were obtained and quantified by Leica TCS NT imaging software for a Leica DM RBE confocal microscope. All data were collected by sequential image recording mode, to prevent 2-photon combination [21].…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…After a final wash, the samples were mounted with VectraShield mounting medium (Vector Laboratories), and images were obtained and quantified by Leica TCS NT imaging software for a Leica DM RBE confocal microscope. All data were collected by sequential image recording mode, to prevent 2-photon combination [21].…”
Section: Study Populationmentioning
confidence: 99%
“…They were washed 3 times with PBS and were incubated with and without M. tuberculosis TN913 (a clinical isolate obtained from the PHRI Tuberculosis Center) at an MOI of 3, with and without fresh PMNs (PMN:THP-1, 3:1) and with and without an insert. After 3 days' incubation, HIV-1 RNA was extracted from the supernatants and was assayed as an HIV-1 load by measurement of HIV-1 complementary DNA by use of real-time quantitative polymerase chain reaction assay performed using ABI Prism 7770, as described elsewhere [20,21].…”
Section: Study Populationmentioning
confidence: 99%
“…In one in vitro study [47], it was observed that MTB increased CXCR4 surface expression on alveolar macrophages and allowed the entry and replication of X4 viruses while inhibiting R5 virus entry. Some earlier studies indicated that macrophages exposed to mycobacterial cell wall lipoarabinomannan become highly susceptible to HIV-1 [48].…”
Section: Discussionmentioning
confidence: 97%
“…Of note, levels of expression of CCR2, the receptor for MCP‐1, on macrophages in PFMC far exceeded that on T‐cells. Whether this indicates a predominant effect of MCP‐1 on transcriptional activation of HIV‐1 in macrophages at sites of MTB infection needs to be addressed considering the extremely high levels of this chemokine in pleural fluid, and with recent data confirming macrophages as a source for HIV‐1 at sites of HIV/TB infection [20, 21] .…”
Section: Discussionmentioning
confidence: 99%